Implementation of Risk Management in Improving the Quality of Educators - Rizal Nurzain; Opik Taupikur Kurahman; Dadan Rusmana (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2026)
The low competence of educators due to mismatched educational backgrounds and lack of adaptation to technological developments poses a serious challenge in the education sector. This phenomenon is exacerbated by the difficulty of finding employment, leading many individuals with certain connections to become educators without adequate mastery of teaching methods. In fact, technology plays a crucial role in supporting students' understanding. Therefore, educators are required to adapt and innovate in developing effective learning methods. This study aims to raise awareness among incompetent and non-adaptive educators about the fatal consequences for future generations, given that students' knowledge, ethics, and social skills are derived from educators. The research method employs a literature study approach, drawing from journals, online media, book reports, and related articles. The results indicate that risk management is necessary to improve educator quality, minimize deficiencies in teaching, knowledge transfer, and learning innovation. In conclusion, risk management plays a vital role in creating a stable and conducive educational environment for the sustainable development of educator quality.